Proceedings of the XII International Symposium on Biological Control of Weeds : La Grande Motte, France, 22-27 April 2007 - Julien, M. H. (CAB books., 2008)
Covering the research findings in various aspects of weed biocontrol, this volume explores weed biology and ecology and the economic impacts, effectiveness and practical implications of weed management strategies. It is of interest to researchers and students in plant and environmental sciences.